The Role of Emotional Intelligence in Effective Leadership: A Review of Contemporary Research - Muhammad Ade Kurnia Harahap; Sutrisno Sutrisno; Devin Mahendika; Suherlan Suherlan; Abu Muna Almaududi Ausat (Al-Buhuts, 2023)
The purpose of this study is to understand the role of emotional intelligence in effective leadership more comprehensively and deeply. This research is qualitative in nature. Data collection techniques included listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The findings of this study conclude that emotional intelligence plays an important role in effective leadership. Leaders who have good emotional intelligence will be better able to manage themselves and others, manage conflict, make wise decisions, and provide appropriate support and motivation to their employees.